Structural features of Fe-Al-vacancy system - Rokhmanov, N.Ya.; Onishchenko, V.V.; Laptev, I.N.; Parkhomenko, A.A. (Functional Materials, 2006)
The influence of structural defects on phase transformation in Fe-Al-vacancies system is considered. It has been shown that, due to existing trend to accumulation of point defects at increasing aluminum content in Fe-Al system alloys, the appearance of ferrite precipitates in Fe₃Al compound becomes thermodynamically favorable in the temperature region of the equilibrium α₁(Fe₃Al)-phase existence.